Diagnósticos de Enfermagem de risco para eventos adversos relacionados à instalação do cateter vesical de demora - BARROS, Lidiane Andréia Assunção (2014)
Bladder Catheterization Delay (BCD) is considered an important resource in health care with wide use in services. It is estimated that about 10% of hospitalized patients make use of this device and is indicated for: control urinary output during the periods trans and post-operative; treatment of diseases that lead to urinary retention; for monitoring in critically ill patients; Stage III and IV of ulcer for sacral pressure or perineal and for patients in urinary incontinence. Among other complications, can cause trauma, pain and bleeding, as well as being strongly associated with Urinary Tract Infection. Considering that the realization of BCD involves risk to patient security, outlined this search, aiming to construct the Nursing diagnoses that presented a risk for adverse event during the installation of bladder catheter, having specific objectives like: identify Nursing actions that presented noncompliance during the installation of bladder catheter and associate the actions identified to the potential impacts described in the literature. The study is characterized in descriptive and exploratory, developed with 06 nurses who realized the insertion of BCD in 56 patients in the operating room of a University Hospital in São Luís/MA. Three instruments were used, as follows: the Instrument A, form composed of sociodemographic data and profile information and professional expertise applied to nurses; the Instrument B, form containing questions related to sex, age and background data of patients and Instrument C, a check list composed for relevant steps to the procedure, filled during the performance of BCD by nurses in the operating room. The quantitative variables were analyzed using descriptive statistics and nursing diagnoses were identified as the shares that were not in compliance during insertion of BCD. For the construction of diagnostic was used the International Classification for Nursing Practice (ICNP). Among the diagnoses of Nursing risk for adverse events related to the insertion of BCD identified, we include: risk for infection; compromised asepsis technique; risk for injury and risk of cross-infection. The actions of Nursing identified as nonconforming with the technique of BCD were: hand hygiene before and after the procedure; guidance, positioning and privacy neglected; failure to use protective eyewear during BCD; aseptic technique not performed during the handling of materials; intimate hygiene in men not fulfilled in the correct sequence; precept of exchange of gases in each step not obeyed; not achieving of the cuff leak test (CLT) before the procedure; probe connection to catcher after insertion; bladder catheter not fixed as recommended; sterile gloves does not removed after the procedure; disposal of perforating-cutting unrealized; record of the procedure not effected. The relevant findings to the technique of insertion of bladder catheter allow us to infer that: despite being a technique widely in-hospital, it is not uncommon to identify actions not in accordance with the technique of BCD reflecting the lack of standardization of procedures among professionals that perform. Thus, patients become targets of errors due to these unsafe practices.